Qualitative and quantitative assessment of posterior segment optical coherence tomography images using standard photos: the Liwan Eye Study. Issue 12 (22nd December 2017) - Wang, Sean K; Guo, Xinxing; Xiao, Ou; Chen, Yanxian; Liu, Ran; Huang, Wenyong; He, Mingguang
Abstract : Background/aims: To develop a standardised grading scheme, using standard photos, for spectral-domain ocular coherence tomography (SD-OCT) images of the posterior eye and evaluate the interobserver agreement among trained ophthalmologists in identifying pathological changes. Methods: Subjects were recruited from Liwan District, Guangzhou, with SD-OCT data collection from June 2013 to November 2013 as part of 10-year follow-up visits from the Liwan Eye Study. All subjects underwent SD-OCT imaging of the macula with scanning lines analysed by two ophthalmologists to assess for the presence of 12 different posterior segment lesions. Per cent agreement for each lesion between the graders and quantitative measures of dome-shaped macula (DSM) height and choroidal thickness were calculated. Results: A total of 679 SD-OCT images from 679 subjects were independently evaluated by the two graders. Each of the 12 lesions was successfully graded as present or absent in over 96% of images. For all lesions, per cent agreement between observers was over 90%, ranging from 90.7% for epiretinal membranes and retinal pigment epithelium thickenings to 99.7% for full thickness macular holes and retinal detachments. Quantitative measurements of DSM height and choroidal thickness at three locations of the eye all exhibited intraclass correlation scores between the two graders of greater than 0.9. Conclusion: Our study demonstrates high concordance between graders in characterising posterior segment lesions using SD-OCT images, validating the continued use of this imaging modality in the diagnosis of posterior eye disease.